Rapid synthesis: Examining the use and implementation of real-time patient feedback programs - DeMaio, P; Dass, R; Bhuiya, AR; Shivji, A; Grewal, E; Bain, T; Chen, K; Alam, S; Wu, N; Wilson, MG (My University, 2024)
An in-depth synthesis of what is known based on the best available global research evidence (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about the use and implementation of real-time patient feedback programs in response to a decision-maker's request.
Keywords: implementation; real-time; patient; feedback; programs